2020
DOI: 10.1017/s0033291719003817
|View full text |Cite
|
Sign up to set email alerts
|

A network investigation of core symptoms and pathways across duration of illness using a comprehensive cognitive–behavioral model of eating-disorder symptoms

Abstract: Background In the past decade, network analysis (NA) has been applied to psychopathology to quantify complex symptom relationships. This statistical technique has demonstrated much promise, as it provides researchers the ability to identify relationships across many symptoms in one model and can identify central symptoms that may predict important clinical outcomes. However, network models are highly influenced by node selection, which could limit the generalizability of findings. The current study (N = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 60 publications
6
39
1
Order By: Relevance
“…Network analyses have identified 'feeling fat' as among the most central eating disorder (ED) symptoms in clinical samples of adults (Christian et al, 2020;Elliott et al, 2020) and children/adolescents (Goldschmidt et al, 2018). These results are consistent with research indicating that 'feeling fat' predicts both ED symptom severity (Linardon et al, 2018) and treatment outcome (Calugi et al, 2018).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Network analyses have identified 'feeling fat' as among the most central eating disorder (ED) symptoms in clinical samples of adults (Christian et al, 2020;Elliott et al, 2020) and children/adolescents (Goldschmidt et al, 2018). These results are consistent with research indicating that 'feeling fat' predicts both ED symptom severity (Linardon et al, 2018) and treatment outcome (Calugi et al, 2018).…”
supporting
confidence: 68%
“…Despite evidence highlighting the relevance of 'feeling fat' to eating pathology, the modest body of extant literature is limited by measurement issues. Indeed, most studies have measured 'feeling fat' using a single item from the Eating Disorders Examination Questionnaire (EDE-Q; Calugi et al, 2018;Christian et al, 2020;Goldschmidt et al, 2020;Levinson et al, 2020;Linardon et al, 2018;Mehak & Racine, 2019). In addition to known limitations of singleitem measures, the EDE-Q only assesses frequency of 'feeling fat' over the past 28 days.…”
mentioning
confidence: 99%
“…The network theory hypothesizes that symptoms influence each other irrespective of traditional diagnosis DSM boundaries (Borsboom, 2017). In network models, ED symptoms such as body checking (Forbush, Siew, & Vitevitch, 2016), fear of weight gain and feeling fat (Christian et al, 2020; Forrest, Jones, Ortiz, & Smith, 2018; Goldschmidt et al, 2018; Levinson, Brosof, Ma, Fewell, & Lenze, 2017) and shape and weight overvaluation (DuBois, Rodgers, Franko, Eddy, & Thomas, 2017; Forrest et al, 2018; Wang, Jones, Dreier, Elliott, & Grilo, 2019; for a review see; Levinson et al, 2018) emerged as the core symptoms with the highest centrality. The authors have interpreted such (statistically) central symptoms as (theoretically) underlying clinical manifestation of ED psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with earlier research from our group [47] patients with LD showed a therapeutic alliance comparable to that of the younger ones. Interestingly, those with a shorter DOI improved less in the drive for thinness and body shape concerns, mirroring a network analysis showing patients with a shorter DOI reporting overvaluation of weight or shape as key elements [48].…”
Section: Accepted Manuscript: Authors' Copymentioning
confidence: 63%